A wireless sensor system for monitoring the performance of a swimmer`s tumble turn - Le Sage, T.; Conway, P.; Cossor, J.; Slawson, S.; West, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
A wireless sensor system has been used to calculate measurable performance parameters throughout a swimmer`s tumble turn. The parameters to be measured have been specified by the users (coaches, biomechanists and swimmers) of the system. The findings suggest that the wireless sensor network can be used to determine the approach time, contact time, glide time, kick time and stroke time to within 0.07 ±?0.16 s of the results obtained using manual digitisation of video images obtained from an underwater camera. It is concluded that it is possible to determine the swimmer`s time, orientation and velocity throughout the turn using the implemented inertial navigation system.